2011
DOI: 10.1128/aac.01330-10
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Meropenem into Epithelial Lining Fluid of Patients with Ventilator-Associated Pneumonia

Abstract: Antibiotic penetration to the infection site is critical for obtaining a good clinical outcome in patients with ventilator-associated pneumonia (VAP). Surprisingly few studies have quantified the penetration of ␤-lactam agents into the lung, as measured by the ratio of area under the concentration-time curve (AUC) in epithelial lining fluid (ELF) to AUC in plasma (AUC ELF /AUC plasma ratio). These have typically involved noninfected patients. This study examines the penetration and pharmacodynamics of meropene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 24 publications
(40 reference statements)
6
98
0
1
Order By: Relevance
“…The exposure targets developed in the murine model to ascertain how well a dose of 2 g of meropenem administered as a 3-h infusion could achieve those targets were simulated. The target attainment of this dosage regimen in achieving a 2-log 10 (CFU/g) cell kill was Ͻ80% at a MIC of 2 g/ml, while values for a 3-log 10 (CFU/g) cell kill and resistance suppression were Ͻ90% at a MIC of 0.25 g/ml and Ͻ75% at a MIC of 1 g/ml (25,26). These findings indicate that PD targets may not be achieved even when the largest licensed dose of meropenem, administered as a prolonged infusion, is prescribed for critically ill patients being treated for VAP, because of the variability of penetration and the high exposure targets for meropenem in ELF in the lungs for this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exposure targets developed in the murine model to ascertain how well a dose of 2 g of meropenem administered as a 3-h infusion could achieve those targets were simulated. The target attainment of this dosage regimen in achieving a 2-log 10 (CFU/g) cell kill was Ͻ80% at a MIC of 2 g/ml, while values for a 3-log 10 (CFU/g) cell kill and resistance suppression were Ͻ90% at a MIC of 0.25 g/ml and Ͻ75% at a MIC of 1 g/ml (25,26). These findings indicate that PD targets may not be achieved even when the largest licensed dose of meropenem, administered as a prolonged infusion, is prescribed for critically ill patients being treated for VAP, because of the variability of penetration and the high exposure targets for meropenem in ELF in the lungs for this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of drug concentrations in the ELF for extracellular respiratory tract pathogens provided the best estimate of antibiotic exposure in this patient population (24). A previous study of meropenem PK in plasma and ELF among seriously ill patients with VAP found the mean plasma CL of meropenem to be variable, due to differing physiological conditions across the patient population, leading to variability in the penetration of this agent into the ELF, with the 10th-to-90th-percentile range of penetration being 3.67% to 177.90%, and inadequate drug exposure at the primary infection site for some patients (25). A study in a murine pneumonia model with P. aeruginosa to determine the penetration of meropenem into the ELF of mice also demonstrated different levels of penetration (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, the median ELF/plasma penetration ratio for meropenem among patients with ventilator-associated pneumonia (VAP) is only 25%. 37 The only way to achieve a favorable fT > MIC PD profile at the site of infection with meropenem is to administer higher doses over prolonged periods of time ( Figure 4). In light of the meropenem ELF data, data available on concentrations at the site of infection, particularly difficult-to-penetrate sites, such as ELF and cerebrospinal fluid, should be considered before designing dosing scheme for implementation into clinical practice.…”
Section: Additional Pharmacokinetic and Pharmacodynamic Considerationsmentioning
confidence: 99%
“…These recommendations are derived from animal experiments; clinical investigations underscore the fact that in sepsis patients, an fT>MIC of 100% elicits a more effective anti-infective effect, and is thus relevant for outcome [190,[201][202][203]. Especially on the basis of striving to achieve adequate tissue concentrations even in deep-lying compartments (pneumonia; bone infections; infections of the central nervous system, CNS)-frequently in the context of disturbed microcirculation in sepsis patients [204][205][206] and also wishing to avoid development of resistance [207,208]-many experts recommend aiming for a concentration of β-lactam antibiotics in the primary compartment (serum/plasma) that exceeds the MIC by 4-times (up to 6-times) for 60-100% of the dosing interval [209]. In addition to individual dosing of antibiotics, the current DGI guideline [124] names therapeutic drug monitoring (TDM) as a possibility for treatment management and reduction of undesirable side effects of antibiotics.…”
Section: Pharmacokinetic Conceptsmentioning
confidence: 99%